The Extent of Implementation of Ra 9211 and P.D. 1619 on Public Secondary Schools in Tampilisan, Zamboanga Del Norte - Mansanadez, Evangeline (JPAIR Multidisciplinary Research, 2019)
Protection against the harmful effect of liquor and cigarette is a government thrust to maintain a healthy living. This study aimed to determine the compliance on the restriction of liquor and cigarette sale to minors within school radius in any schools in Tampilisan, Zamboanga Del Norte. It employed a descriptive survey method of research using a questionnaire to gather data; employing Chi-square test in finding the difference on the perception of respondents; utilizing the 244 PNP personnel, barangay officials, and community people. This study answered the questions on the extent of compliance on the restriction of liquor and cigarette sale to minors and tested the hypothesized difference on the perception of respondents. Findings led to the conclusion that the extent of compliance on the sale of liquor to minors is to a small extent while on cigarettes is to a moderate extent. Pearson Chi-square test indicated that there is a highly significant difference on the perception of the three groups of respondents on the extent of compliance on the sale of liquor to minors based on barangay ordinance and a significant difference based on school policies. On the sale of cigarettes, there exists a highly significant difference in their perception. Thus, a concerned community that aimed for the betterment of the youth for today and the incoming generations produces a peaceful, sound, and a healthy environment.